Pro-Women Legal Reform in Morocco: Is Religion an Obstacle? - Imane Chaara (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The question of the role of modern law in triggering social change is of particular importance in societies where customs and norms support the marginalization of some social groups. The conventional view is that the success of the formal law is constrained by the system of informal rules and values which support the prevailing customs, and the law therefore appears as a 'dead letter'. Aldashev et al (2011) mitigate this pessimistic scenario by formally showing that the law has, under certain conditions, the effect of making the custom evolve in the direction of the law. One of the conditions to achieve this effect is the identification of agents with the new law. In this paper, we focus on the adherence of agents to a pro-women legal reform in Morocco, the reform of the Family Code which is religious-inspired legislation. We use a unique database created from a survey we conducted in Morocco in 2008 to provide some evidence about the factors which drive conservative positions with respect to a progressive legal reform. We observe that women who are benefiting from the reform are not unanimously in favour of it. Conversely, a non-negligible part of the male population strongly supports the new legislation. In order to explain these behaviours, we mainly focus on three specific factors: education, location and religion. Contrary to what naïve beliefs would suggest - rural men with a low level of education and intense religious practice express a lower support to the new Family Code -, we find that there is no straightforward relation between the three aforementioned factors (education, location and religion) and the support of the new legislation. Another precondition to the effect stressed by Aldashev et al. (2011) is that agents have sufficient information about the law. The data analysis leads to an unexpected finding: living in rural areas is, in some cases, positively and significantly associated with a higher probability of being properly informed than living in Casablanca city, the economic centre of the country.
Keywords: 330